Outdoor cooling and heating design values for energy management in Nigeria’s air-conditioning industry - Ishola I. S.; Adeyemi K. O.; Ozigis I. I.; Zarmai M. T. (Cogent Engineering, 2025)
This study establishes location-specific cooling and heating design values to optimize Heating, Ventilation, Air Conditioning, and Refrigeration (HVACR) systems in Nigeria, using 23 years of high-resolution hourly climatic data obtained from NASA for Lagos and Abuja. Key climatic parameters analyzed include dry-bulb temperature, wet-bulb temperature, and relative humidity to determine percentile-based outdoor design conditions essential for energy-efficient HVACR operations. The findings reveal significant climatic variations between the two cities. Lagos shows January outdoor dry-bulb temperatures of 30.2 °C, 30.05 °C, 29.99 °C, 29.64 °C, and 29.16 °C at 0.4%, 1%, 2%, 5%, and 10% occurrence frequencies, respectively. In contrast, Abuja records higher values of 35.69 °C, 34.71 °C, 34.34 °C, 33.89 °C, and 32.84 °C for the same percentiles. These differences necessitate climate-responsive HVACR strategies: Lagos, with its stable and humid climate, requires systems prioritizing dehumidification and moderate cooling, while Abuja’s dry and variable conditions support evaporative cooling in dry seasons and traditional air conditioning during rains. Incorporating these tailored design values can significantly enhance system efficiency, reduce energy consumption and operational costs, and contribute to sustainable building practices across Nigeria’s climatic zones. The study recommends periodic updates and real-time field validation to ensure continued relevance under changing climate conditions.